Ocular Component Development during Infancy and Early Childhood - Mutti, Donald O.; Sinnott, Loraine T.; Lynn Mitchell, G.; Jordan, Lisa A.; Friedman, Nina E.; Frane, Sara L.; Lin, Wendy K. (Optometry and vision science, 2018)
SIGNIFICANCEThe study fills an important gap by providing a longitudinal description of development of the major structural and optical components of the human eye from 3 months to nearly 7 years of age. Normative development data may provide insights into mechanisms for emmetropization and guidance on intraocular lens power calculation. PURPOSEThe purpose of this study was to describe the pattern of development of refractive error and the ocular components from infancy through early childhood. METHODSCycloplegic retinoscopy (cyclopentolate 1%), keratophakometry, and ultrasonography were performed longitudinally on between 162 and 293 normal birth weight infants at 0.25, 0.75, 1.5, 3, 4.5, and 6.5 years of age. RESULTSRefractive error and most ocular components displayed an early exponential phase of rapid development during the first 1 to 2 years of life followed by a slower quadratic phase. Anterior and vitreous chamber depths, axial length, and crystalline lens radii increased at every visit. The crystalline lens thinned throughout the ages studied. The power of the cornea showed an early decrease, then stabilized, whereas the crystalline lens showed more robust decreases in power. The crystalline lens refractive index followed a polynomial growth and decay model, with an early increase followed by a decrease starting at 1 to 2 years of age. Refractive error became less hyperopic and then was relatively stable after 1 to 2 years of age. Axial lengths increased by 3.35 ± 0.64 mm between ages 0.25 and 6.5 years, showed uniform rates of growth across the range of initial values, and were correlated with initial axial lengths (r = 0.44, P < .001). CONCLUSIONSEarly ocular optical and structural development appears to be biphasic, with emmetropization occurring within the first 2 years of infancy during a rapid exponential phase. A more stable refractive error follows during a slower quadratic phase of growth when axial elongation is compensated primarily by changes in crystalline lens power.